A systematic review and thematic synthesis of qualitative studies exploring GPs' and nurses' perspectives on discussing weight with patients with overweight and obesity in primary care. (6th December 2020) - Warr, William; Aveyard, Paul; Albury, Charlotte; Nicholson, Brian; Tudor, Kate; Hobbs, Richard; Roberts, Nia; Ziebland, Sue
Summary: Guidelines and evidence suggest primary care clinicians should give opportunistic interventions to motivate weight loss, but these rarely occur in practice. We sought to examine why by systematically reviewing qualitative research examining general practitioners' ('GPs') and nurses' views of discussing weight with patients. We systematically searched English language publications (1945‐2018) to identify qualitative interview and focus group studies. Thematic methods were used to synthesise the findings from these papers. We synthesised the studies by identifying second‐order themes (explanations offered by the original researchers) and third‐order constructs (new explanations which went beyond those in the original publications). Quality assessment using the Joanna Briggs checklist was undertaken. We identified 29 studies (>601 GPs, nurses and GP trainees) reporting views on discussing weight with patients. Key second‐order themes were lack of confidence in treatments and patients' ability to make changes, stigma, interactional difficulty of discussing the topic and a belief of a wider societal responsibility needed to deal with patients with overweight and obesity. The third‐order analytical theme was that discussions about weight were not a priority, and other behavioural interventions, including those relating to smoking, often took precedent. GPs and nurses reported that noting body mass index measurements at every consultation alongside a framework to deliver interventions would likely increase the frequency and perceived efficacy of behavioural weight interventions. GPs and nurses acknowledge the importance of obesity as a health issue, but this is insufficient, particularly amongst GPs, for them to construe this as a medical problem to address with patients in consultations. Strategies to implement clinical guidelines need to make tackling obesity a clinical priority. Training to overcome interactional difficulties, regular weighing of patients and changing expectations and understanding of weight loss interventions are also probably required.